Narratives of work injuries as a basis for improving preventive measures - Fubini, Lidia; Pasqualini, Osvaldo; Gilardi, Luisella; Ferro, Elisa; Marino, Maurizio; Santoro, Silvano; Tosco, Eleonora; Bena, Antonella; Coffano, Maria Elena (La Medicina del Lavoro, 2016)
Background: Many authors consider  narrative descriptions of injuries gathered by OSH inspectors  extremely important  in identifying causes,   setting  priorities and drawing up intervention strategies. Narratives provide additional insight regarding complex behaviour, attitudes and interactions, which help to understand the decision patterns and the context of the injury. Storytelling is an effective way of sharing and remembering information. Objective: The main aim  was to describe the experience of collecting stories from injury investigation reports, backed up by systematic prevention guidelines, that will improve information sharing by means of a knowledge transfer method based on storytelling. Methods: OSH operators from Health Units, who were invited to provide the injury stories, were enrolled through educational workshops aimed at selecting the injuries to relate following the sentinel event approach, using an effective style of writing, identifying the key elements of the story and  using witnesses’ narratives to study in depth  the critical points identified during the investigation. Results: 110 OSH operators voluntarily joined the project between 2012 and first half of 2015. 33 injury stories were collected, discussed and published on Dors’ website http://www.dors.it/storiedinfortunio. Conclusions: The results show that  prevention and protection  measures do indeed benefit from a narrative-based approach,  so that health and safety can be viewed in a more comprehensive way by  facilitating  knowledge improvement and sharing.